Fitoalimurgia e sustentabilidade: potencial tecnológico e alimentício das plantas alimentícias não convencionais (PANC) Pereskia aculeata Mill. e Cyperus esculentus L. cultivadas no Ceará - Sá, Kellen Miranda (2025)
Non-Conventional Food Plants (NCFP) have great potential to diversify the diet and contribute to food security in Brazil. Many of these species, in addition to being nutritionally richer than conventionally cultivated plants, are found in the phytoalumurgical field, meaning they grow spontaneously as weeds and are widely adapted to the local soil and climate. The cactus Pereskia aculeata Mill. (ora-pro-nóbis) and the sedge Cyperus esculentus L. (yellow sedge) are two NCFP found in the Northeast with potential for inclusion in the local population’s daily diet, as they are widely distributed throughout the region and resistant to the semiarid climate. This research focused on the field of phytoalumnitherapy to investigate and understand the chemical-technological, nutritional, sensory, and market potential of NCFP (plants of the genus P. aculeata) and C. esculentus (tubers) cultivated in Ceará. It addressed the development of a mixed food product, focusing on promoting food security and sustainability in the region. Methodologically, this is a prospective, exploratory-descriptive, and experimental study with a qualitative and quantitative approach. Considering its multidimensional focus, the study assumed the premise of complementarity, where limitations were minimized by a combination of techniques. To characterize the plant raw materials and the products, botanical, chemical, biological, physical, and bioinformatics analyses were performed. To holistically understand trends, motivations, and related market factors, scientometric analyses, a survey, and a focus group were conducted. The city of Fortaleza was selected for the survey and focus group. Experimental trials showed that locally cultivated C. esculentus tubers can be accessible sources of carbohydrates (49.93%), lipids (19.27%), and fiber (13.56%), phytochemically containing sterols, triterpenes, and alkaloids. P. aculeata leaves can serve as a source of protein (20.18%), fiber (10.86%), and flavonoids (56,90mg/100g), phytochemically containing alkaloids, steroids, triterpenes, tannins, and heterosides. By combining these two NCFP in different proportions with wheat flour, the nutritional profile of the resulting blended flours and developed products was improved, especially in fiber, protein, lipids, phenolic compounds, and energy value. Technologically, these blended flours interfered gluten network formation, resulting in changes in dough rheological (farinographic and extensographic) and colorimetric parameters, limiting their applications. These changes did not hinder the production of cookies with good sensory and technological acceptance. These findings corroborate market research, which found that research trends for these NCFP encompass antioxidant activity, physical properties, proteins, and starch. This antioxidant activity also determined acceptance among the interviewed population, which consumes innovative foods and products with a primary focus on health. However, there is no widespread recognition of these phytoalimurgy/NCFP species as a food source, as most interviewees are unfamiliar with them, reflecting a lack of awareness of the surrounding biodiversity. This appears to be the main driver of the prejudice and neglect associated with NCFP, where hedonic experiences with NCFP (and their products) can inform understandings of the sociocultural and cognitive variables that influence emotional and behavioral consumer responses. The conclusion is that the species P. aculeata and C. esculentus are viable for food science and technology and are important for food and nutritional security in semiarid regions. They also have the potential to be incorporated into the population’s diet. Their uses can promote regional development, as well as healthy, safe, sustainable, and innovative diets. It is important to emphasize that further studies are important to promote better use of these species in food science and technology.